2017
DOI: 10.1021/acs.energyfuels.7b03147
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Gasification of Sugar Cane Bagasse: Quantitative Understanding of Kinetics and Catalytic Roles of Inherent Metallic Species

Abstract: A total of 18 chars from the pyrolysis of six trios of sugar cane bagasses (SCBs; original, water-washed, and acid-washed) were gasified with CO2 at 900 °C, aiming at a quantitative description of the rate of gasification catalyzed by inherent metallic species and a correlation of the catalytic activity and its change during the gasification with the metallic species composition. The measured kinetics was described quantitatively over a range of char conversion, 0–0.999, by a model that assumed progress in par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(49 citation statements)
references
References 37 publications
2
43
0
Order By: Relevance
“…Note that not only AAEM but also Fe species are inherent in the LY char . Its catalytic effect was, however, very limited as a result of the lower activity than AAEM species as well as rapid deactivation. ,, …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Note that not only AAEM but also Fe species are inherent in the LY char . Its catalytic effect was, however, very limited as a result of the lower activity than AAEM species as well as rapid deactivation. ,, …”
Section: Resultsmentioning
confidence: 99%
“…] , vary along with the gasification, influencing the kinetics. Recent studies on CO 2 gasification of chars from lignites and biomass reported that the rate of gasification was described well by the following equation: where X , k 1 , and k 2 are the char conversion and rate constants for non-catalytic gasification and catalytic gasification, respectively. It assumes the non-catalytic and catalytic reactions in parallel.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zahara et al ( 10.1021/acs. energyfuels.7b03147) 23 from the combustion of a single coal char particle under oxyfuel conditions. Li et al (10.1021/acs.energyfuels.7b03105) 31 report the effect of acidic gases (NO x and SO 2 ) on the removal of Hg 0 in an oxy-fuel CO 2 compression process.…”
mentioning
confidence: 99%